Resistance and thermopower in Bi wires with trigonal orientation - Kobileanscaia (Ţurcan), Ana (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2013)
The results of investigation of the resistance and thermopower anisotropy in Bi wires with different diameters in a temperature range of 4.2–300 K are described. Single-crystal Bi wires in a glass capillary with the (1011) crystallographic orientation are prepared by liquid phase casting by the Ulitovsky method, and the wires with trigonal orientation are prepared by the method of zone recrystallization with a seeding agent. Single-crystallinity and crystallographic orientation of the wires are reliably determined by X ray diffraction, angle rotation diagrams of transverse magnetoresistance, and Shubnikov de Haas (ShdH) oscillations. It is shown that the different manifestation of a quantum size effect in Bi wires with d ≈ 0.5 μm with the trigonal and standard (1011) orientations leads to thermopower anisotropy that achieves a value of 100–120 μV/K and resistivity anisotropy ρ in a temperature range of 50–100 K, which substantial exceed the anisotropy in pure Bi.